Modeling electrical characteristics of thin-film field-effect transistors I. Trap-free materials - Stallinga, Peter (2015)
A new analytical model is developed for thin-film field-effect transistors (TFTs). The active layer of the devices is considered purely two-dimensional. In the first part, the basic model is developed for intrinsic materials. It is demonstrated that it accurately describes the electrical characteristics and elucidates on the physical meaning of the device and material parameters, such as threshold voltage and sub-threshold current. It also clarifies the nature of so-called contact effects, often used in literature to explain non-linear I-V curves. Furthermore, ambipolar devices are treated. (c) 2006 Elsevier B.V. All rights reserved.